POST-PANDEMI COVID-19 BREAD MSME MARKETING STRATEGY - Herdiana Dyah Susanti; Dian Arief Pradana; Mahfud Mahfud (International Journal of Artificial Intelligence Research, 2022)
The covid-19 pandemic has had an impact on life as well as business. Good marketing means having a deep understanding of potential customers where many potential customers have changed due to the Covid-19 pandemic. The company needs to analyze the different marketing channels it currently has in the market and focus more on the channels that get more customer attention. The development of MSMEs in the culinary field in Banyuwangi is currently starting to develop. One of them is UMKM that produces home-made bread, namely Jessica Bakery. As many home-baked MSMEs have emerged, entrepreneurs are required to be more creative in designing and deciding on marketing strategies to be implemented in order to compete. The aim of this study is to find out the best alternative marketing strategies that can be used in UMKM